Chronology and documentary handbook of the State of Mississippi - Vexler, Robert I. (Chronologies and documentary handbooks of the States ;, 1978)
Contains a chronology of historical events in Mississippi, a biographical directory, the State constitutions of 1817 and 1868, and selected documents pertinent to Mississippi history.